Assessing the Suitability of Communal Toilet Models for Achieving the Sustainable Development Goals in Urban Settlements of West Java - Yenita Sandra Sari; Didi Dwi Anggoro; Hussein Alkhozahe; Cenap Ozel (International Journal of Environmental, Sustainability and Social Science, 2026)
This study investigates communal toilet models as an alternative sanitation soliution for densely populated urban settlements and their potential contribution to sustainable development targets related to safe sanitation. In many high-density settlements, limited land availability and infrastructure constraints prevent households from having private sanitation facilities, leading communities to rely on shared sanitation systems. This resarch applies a mixed-method approach combining quantitative and qualitative data. Primary data were collected from four sub districts in Bandung, Wes Java, Indonesia, involving 40 household respondents and 100 key informarmants during the period 2024-2025. Additional information on social, economic, and demographic characteristics was obtained through structured questionnaires. The analysis evaluates communal toilet construction models that consider land availability and water supply conditions, as well as two waste treatment scenarios designed for facilities serving up to 120 users. The results indicate that the second scenario provides greater flexibility in spatial adaptation and more manageable waste treatment for dense settlements. The findings emphasize that appropriate design, effective waste management, accessibility, and affordability are essential factors for improving sanitation services in high-density urban areas. This study highlights the importance of adaptive communal sanitation systems as a practical approach to expanding sanitation access and supporting sustainable urban development in densely populated settlements.